2021
DOI: 10.25133/jpssv302022.009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity Among University Students in Indonesia from Before to During the COVID-19 Pandemic: A Retrospective Cohort Study

Abstract: University life is an important phase for forming healthy physical activity habits among university students. However, little is known about the change in physical activity level during the COVID-19 pandemic among university students in Indonesia, which has a low stringency index. A retrospective cohort study was conducted among students of Universitas Gadjah Mada (n=153) from October to November 2020, where there were asked to recall their physical activity level and type of physical activity engaged in at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Our study also strengthens that BMI and field of study are important predictors of PA among university students. This study strengthens our previous research on the early pandemic, which found an increase in PA among non-health natural sciences students compared to the other fields of study (Rizal and Wibowo, 2021). However, our current study contradicts the majority of previous studies showing that overweight and obese adults were associated with lower PA levels (Haynes et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our study also strengthens that BMI and field of study are important predictors of PA among university students. This study strengthens our previous research on the early pandemic, which found an increase in PA among non-health natural sciences students compared to the other fields of study (Rizal and Wibowo, 2021). However, our current study contradicts the majority of previous studies showing that overweight and obese adults were associated with lower PA levels (Haynes et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…However, it could be caused that the opportunity lost was compensated by the more available time to engage in PA since the majority of our samples felt that they had more time to be physically active (Yon et al, 2022). In addition, most of our samples also felt they did not lose their enjoyable PA types, which indicate they could engage in their favorite PA or find new PA routines even if they lost opportunities to engage in certain kind of PA, such as sports (Rizal and Wibowo, 2021;Yon et al, 2022).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Physical exercise has the lowest mean score compared to other daily health practices. Another study found that the frequency of physical exercise among students decreased during the COVID-19 pandemic, e.g., in Europe and Northern America [ 39 ] and also in Indonesia [ 40 ]. Therefore, relevant health promotion is needed so that students can be physically active during the pandemic in order to increase their healthy immune system.…”
Section: Discussionmentioning
confidence: 99%